2013
DOI: 10.1039/c3cc40732b
|View full text |Cite
|
Sign up to set email alerts
|

Laser wavelength- and power-dependent plasmon-driven chemical reactions monitored using single particle surface enhanced Raman spectroscopy

Abstract: Plasmon-driven chemical reaction of p-nitrothiophenol (pNTP) dimerizing into p,p'-dimercaptoazobenzene (DMAB) has been monitored using single particle surface enhanced Raman spectroscopy, which provides laser wavelength- and power-dependent conversion rates of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
132
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 21 publications
(22 reference statements)
11
132
0
3
Order By: Relevance
“…[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] Although it has been reported that it is possible to produce azobenzene derivatives from aromatic nitro and amine compounds, the reaction mechanism is not clear. Zhao et al explained the selective formation of azobenzene derivatives from p-substituted nitrobenzenes and anilines using the photoinduced charge transfer model based on TDDFT methods (Figure 9c).…”
Section: Wwwadvopticalmatdementioning
confidence: 96%
See 3 more Smart Citations
“…[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] Although it has been reported that it is possible to produce azobenzene derivatives from aromatic nitro and amine compounds, the reaction mechanism is not clear. Zhao et al explained the selective formation of azobenzene derivatives from p-substituted nitrobenzenes and anilines using the photoinduced charge transfer model based on TDDFT methods (Figure 9c).…”
Section: Wwwadvopticalmatdementioning
confidence: 96%
“…These parameters strongly affect the exact role and ability of hot electron in the chemical reaction. [74,83,84] Dong et al reported the substrate-, wavelength-, and time-dependent catalytic conversion of pNTP to DMAB on different metallic films, such as Au, Ag, and Cu. [74] When Cu films were irradiated by light with an incident wavelength of 632.8 nm, the SERS spectra remained almost unchanged for the whole reaction time (>2 h), However, they were dramatically changed when the incident wavelength was changed to 514.5 nm.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 2 more Smart Citations
“…根据 PATP 在银金等金属纳米结构表面转化为 DMAB 的反应与激发光波长 [70,132] 、激发光功率 [98,133] 光照时间 [73,98] 、环境气氛 [134,135] 、溶液酸碱性 [64~67] 等实 验条件的依赖关系, 我们发展了研究等离激元光催化反 应的理论模型, 提出了 PATP 在固气界面和固液界面发 生表面催化偶联反应转化为 DMAB 的反应机理 [136,137] , 如图 9 所示. 等离激元纳米结构上的光催化反应与传统 半导体材料上的光催化反应最大的区别是, 等离激元纳 米结构通过 SPR 对可见光具有高效的吸收, 并且通过非 辐射弛豫产生能级高于金属费米能级的"热电子"及能 级低于金属费米能级的"热"空穴.…”
Section: 反应机理unclassified